Impact of JICA Programme on Sericulture Development in Tamil Nadu - M.T. Himantharaj,; G. Srinivasa,; R. Gnanashekaran,; G.S. Vindhya, (Journal of Agricultural Extension Management, 2025)
Sericulture is a highly remunerative agro-based enterprise, characterized by fast income turnover. It provides regular employment to rural households, has a shorter gestation period and provides higher returns as compared to major agriculture crops. Sericulture has been adjudged as one of the means of rural development by the planners (Raveendra Mattigatti & Iyengar, 1995). The commercial silkworms are generally classified as multivotine and bivoltine. The multivoltines are those which complete more than two life cycles in a year in natural conditions. The bivoltine completes two life cycles in a year in natural conditions and is considered to be providing raw silk which is qualitatively superior